Old but still good: genetic diversity of ancient pecan genotypes from southern Brazil - LUANA O. OLIVEIRA; DANIELE D. SANTOS; DALVAN C. BEISE; TALES POLETTO; IGOR POLETTO; MARLOVE F.B. MUNIZ; JOANA N.O. ZEIST; VALDIR M. STEFENON (Anais da Academia Brasileira de Ciências, 2023)
Abstract Pecan [Carya illinoinensis (Wangenh.) K. Koch] is a crop fruit native to the USA and Mexico currently cultivated in several countries, including Brazil, Uruguay, Argentina, Chile, Peru, China, South Africa, and Australia. Supported by the increasing consumption and market prices, the interest in the cultivation of this fruit crop is strongly growing around the world. In this study, AFLP and S-SAP markers were employed to characterize the genetic diversity of ancient accessions of pecan from southern Brazil. The evaluated plants were selected and preserved by the farmers and are remnants of the first introduction of seedlings from the U.S.A into southern Brazil aiming at developing research towards establishing commercial orchards. High levels of genetic diversity were estimated, suggesting that these plants have an important genetic background for the establishment of a germplasm collection with a wide genetic basis, for the development of breeding programs for this fruit crop. Cluster analysis of the genetic datasets revealed some correlation between the nuts’ morphometric traits and genetic markers. Such correlation should be further exploited. These ancient genotypes must be evaluated for other agronomic traits of interest and included in core collections of pecans.